Numerical analysis on maneuverability of amphibious rescue boat in restricted waters - Jiadong WEN; Jiangyan SHAO; Qipeng CHENG; Weiqin LIU; Xuming WANG (Zhongguo Jianchuan Yanjiu)
ObjectivesTo study the maneuverability of amphibious rescue boats in restricted waters, a method for predicting maneuvering motion is proposed and the maneuvering performance of rescue boats in nearshore and shallow waters is investigated.MethodsA CFD-based maneuverability analysis method is adopted to solve the hydrodynamic characteristics of amphibious rescue boats and analyze their maneuvering performance in restricted waters through maneuvering motion equations. For the analysis of the maneuverability of amphibious rescue boats in restricted waters, a fourth-order Runge-Kutta maneuvering motion equation solver is independently developed, then verified and applied to analyze the turning performance and correction capabilities of rescue boats in nearshore and shallow waters. ResultsThe results show that when the nearshore distance decreases to 1.2 times the beam of the boat, the tactical diameter decreases by 5.86%, the turning performance is improved, and the maneuverability is halved; when the water depth to draft ratio decreases to 1.2, the tactical diameter of the boat increases by 1.5 times, and the turning performance is significantly decreased, and the bow turning lag time disappears. ConclusionsThe results of this study indicate that the proposed method can be used to predict the maneuvering motion of rescue boats in restricted waters and is suitable for the optimization of the maneuverability design of rescue boats.